Kurt Yaghjian to play Amahl in the Christmas play, "Amahl and the Night Visitors," 1965. - (:unkn) unknown (Forsyth County Public Library, 2008)
WSJ 12-12-65 p.A3.
Kurt Yaghjian to play Amahl in the Christmas play, "Amahl and the Night Visitors," 1965. Kurt is a student at the School of the Arts.
Keywords: Forsyth County (N.C.) -- History -- Pictorial works; Forsyth County (N.C.) -- History -- Sources; Digital Forsyth